DIFFERENTIATION OF LEUKOCYTES OF NILE TILAPIA (Oreochromis niloticus) WITH FEED CONSIST OF NONI FRUIT FLOUR (Morinda citrifolia L) - Memi Martin Ilmayati; Henni Syawal; Adelina ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on 10th June until 24th July 2015. The aims ofthis research was to determine the best dose of noni fruit flour (Morinda citrifolia L)addition in feed to increase immunity of nile tilapia (Oreochromis niloticus) by S.iniae. This research used Completely Randomized Design (CRD) with one factor,five treatments and three replications. The treatments were addition of noni fruit flourin the feed with different concentration i.e : Kn (without addition of noni fruit flourand without infected by S. iniae), Kp (without addition of noni fruit flour and infectedby S. iniae), P1 (addition of noni fruit flour 3 g/kg of feed and infected by S. iniae), P2(addition of noni fruit flour 6 g/kg of feed and infected by S. iniae) and P3 (additionof noni fruit flour 9 g/kg of feed and infected with S. iniae). Noni fruit flour giventhrough artificial feed with 30% of protein content. The results showed that noni fruitflour in feed of treatment P3 on the best dose (9 g/kg of feed) was total leukocytes73.720 cell/mm3, lymphocytes 66.33%, monocytes 29.33%, neutrophils 4.33%, theaverage of weight 24.06 g and survival rate 91.67%.Key word : Differentiation of leukocytes, Morinda citrifolia L, Oreochromisniloticus, Streptococcus iniae,